2016
DOI: 10.1111/1755-0998.12533
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the movement and spawning activity of bigheaded carps with environmental DNA

Abstract: Bigheaded carps are invasive fishes threatening to invade the Great Lakes basin and establish spawning populations, and have been monitored using environmental DNA (eDNA). Not only does eDNA hold potential for detecting the presence of species, but may also allow for quantitative comparisons like relative abundance of species across time or space. We examined the relationships among bigheaded carp movement, hydrography, spawning and eDNA on the Wabash River, IN, USA. We found positive relationships between eDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 48 publications
2
65
0
Order By: Relevance
“…A recent study demonstrated that the existence of target DNA was correlated with the migration range of anadromous fish (Yamanaka & Minamoto, ). Another study demonstrated a significant positive correlation between DNA concentration and the number of bighead carp detected by telemetry in a spawning habitat in which the increase in DNA was presumably attributable to the individuals that migrated for spawning (Erickson et al., ). These studies, together with the present study, suggest the great potential of the eDNA method for monitoring seasonal animal movement.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the existence of target DNA was correlated with the migration range of anadromous fish (Yamanaka & Minamoto, ). Another study demonstrated a significant positive correlation between DNA concentration and the number of bighead carp detected by telemetry in a spawning habitat in which the increase in DNA was presumably attributable to the individuals that migrated for spawning (Erickson et al., ). These studies, together with the present study, suggest the great potential of the eDNA method for monitoring seasonal animal movement.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the D-loop region is useful as a genetic marker because it is thought to be highly species specific, although it requires more careful attention in the selection of conserved sites when designing primers, because it has higher intraspecific diversity than other regions. A few studies also suggested that nuclear DNA also sensitive genetic marker for species identification in eDNA studies (Erickson et al, 2016;Minamoto et al, 2017). The species-specific primer is carefully designed either manually or available software, such as Primer 3 (Rozen & Skaletsky, 2000), Primer Express (Gene Codes Corporation, Ann Arbor, MI) or ecoPCR (Ficetola et al, 2010).…”
Section: Species-specific Detectionmentioning
confidence: 99%
“…Despite this, degree of correlation between eDNA concentration and abundance demonstrated in the field is variable between studies. A recent study of a stream‐dwelling char demonstrated a high correlation (Wilcox et al, ), but other studies reported marginally significant correlations or secondary contribution of abundance to eDNA amount (Doi et al, ; Erickson et al, ; Lacoursière‐Roussel, Côté, Leclerc, & Bernatchez, ; Klobucar, Rodgers, & Budy, ; Nevers et al, ; Pilliod, Goldberg, Arkle, Waits, & Richardson, ; Thomsen et al, ; Yamamoto et al, ). In some studies, eDNA concentration did not correlate with the biomass of the target animals (Biggs et al, ; Spear, Groves, Williams, & Waits, ).…”
Section: Introductionmentioning
confidence: 99%